Complications of abortion and need for appropriate ultrasound assessment and peri‐abortion care. (19th April 2021) - Wang, Mandy; Girgis, Myriam; Cohen, Sally; Lee, Joseph
Abstract : Abortion is an essential medical service; however, the lack of standardised protocols and follow‐up can cause unintended harm. We present four cases of post‐abortion complications presenting to a Sydney tertiary hospital which could have been avoided by appropriate ultrasound prior to abortion and peri‐abortion care. While social progress has led to significant reforms in abortion law, clinical guidelines must also be updated and consistently applied to ensure safety of this practice.